New investigations at the Middle Stone Age site of Pockenbank Rockshelter, Namibia - Schmidt, Isabell; Bubenzer, Olaf (Antiquity, 2016)
In southern Africa, Middle Stone Age sites with long sequences have been the focus of intense international and interdisciplinary research over the past decade (cf. Wadley 2015). Two techno-complexes of the Middle Stone Age—the Still Bay and Howiesons Poort-have been associated with many technological and behavioural innovations of Homo sapiens. The classic model argues that these two techno-complexes are temporally separated ‘horizons’ with homogenous material culture (Jacobs et al.2008), reflecting demographic pulses and supporting large subcontinental networks. This model was developed on the basis of evidence from southern African sites regarded as centres of subcontinental developments.
Gesehen am 17.03.2017